2010
DOI: 10.1159/000314610
|View full text |Cite
|
Sign up to set email alerts
|

Which Treatment to Choose for Portal Biliopathy with Extensive Portal Thrombosis?

Abstract: Background: Portal biliopathy refers to abnormalities of the biliary tract developing in relation to portal hypertension. Portosystemic splenorenal or mesenterico-caval shunting is a safe and effective method to relieve biliary obstruction in symptomatic patients but is unfeasible in cases of extensive thrombosis of the splenic and superior mesenteric veins. In such cases, a makeshift portosystemic shunt between a suitable portal varix and the caval system can be an interesting alternative. Methods: This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…We found that the successful response to EBD in jaundiced patients with bile duct invasion of HCC depended upon relatively mild jaundice and preserved liver function and intact portal vein flow. These results can be supported by the findings that the damage to the liver reduces the elimination of bilirubin from the body [17] and portal biliopathy per se in relation to extensive thrombosis of the portal system induces deep chronic jaundice [18,19]. In addition, appropriate palliation by EBD increased the probability of receiving essential treatment for HCC and further resulted in favorable survival outcomes, regardless of pre-procedural bilirubin concentration.…”
Section: Discussionmentioning
confidence: 89%
“…We found that the successful response to EBD in jaundiced patients with bile duct invasion of HCC depended upon relatively mild jaundice and preserved liver function and intact portal vein flow. These results can be supported by the findings that the damage to the liver reduces the elimination of bilirubin from the body [17] and portal biliopathy per se in relation to extensive thrombosis of the portal system induces deep chronic jaundice [18,19]. In addition, appropriate palliation by EBD increased the probability of receiving essential treatment for HCC and further resulted in favorable survival outcomes, regardless of pre-procedural bilirubin concentration.…”
Section: Discussionmentioning
confidence: 89%
“…In cases in which PB is due to biliary compression by PC, the detension of collateral vessels obtained with the reduction of portal pressure by PSS can resolve in the same time biliary obstruction[30]. The most common PSS performed are proximal spleno-renal shunt or mesocaval shunt, but other types of surgical shunts include meso-gonadal vein shunt, meso-renal shunt, right-porto ovarian shunt, shunt between a portal varix and cava[41,48-51]. …”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In patients with symptomatic PB, other variant forms of PSS can be performed with good results. Particularly, shunts between a splanchnic varix and the inferior vena cava or the left renal vein have also been described [32]. In patients with no vein available for shunt, a splenectomy with devascularization may alter the natural history of PB, probably by decreasing overall portal flow, and can thus be considered as a therapeutic procedure [33].…”
Section: Surgical Treatmentmentioning
confidence: 99%